Targeted delivery of oral vaccine antigens to aminopeptidase N protects pigs against pathogenic E. coli challenge infection - Van der Weken, Hans; Jahantigh, Hamid Reza; Cox, Eric; Devriendt, Bert (Frontiers in Immunology, 2023)
Oral subunit vaccines are an interesting alternative strategy to traditional live-attenuated or inactivated vaccines for conferring protection against gut pathogens. Despite being safer and more cost-effective, the development of oral subunit vaccines remains challenging due to barriers imposed by the gastrointestinal tract, such as digestive enzymes, a tolerogenic immune environment and the inability of larger proteins to cross the epithelial barrier. Recent advances have focused on overcoming these barriers by using potent mucosal adjuvants or pH-responsive delivery vehicles to protect antigens from degradation and promote their release in the intestinal lumen. A promising approach to allow vaccine antigens to pass the epithelial barrier is by their targeting towards aminopeptidase N (APN; CD13), an abundant membrane protein present on small intestinal enterocytes. APN is a peptidase involved in digestion, but also a receptor for several enteric pathogens. In addition, upon antibody-mediated crosslinking, APN facilitated the transport of antibody-antigen fusion constructs across the gut epithelium. This epithelial transport resulted in antigen-specific immune responses. Here, we present evidence that oral administration of APN-specific antibody-antigen fusion constructs comprising the porcine IgA Fc-domain and the FedF tipadhesin of F18-fimbriated E. coli elicited both mucosal and systemic immune responses and provided at least partial protection to piglets against a subsequent challenge infection with an F18-fimbriated STEC strain. Altogether, these findings will contribute to the further development of new oral subunit vaccines and provide a first proof-of-concept for the protective efficacy of APN-targeted vaccine antigens.